Infarct in a New Territory After Treatment Administration in the ESCAPE Randomized Controlled Trial (Endovascular Treatment for Small Core and Anterior Circulation Proximal Occlusion With Emphasis on Minimizing CT to Recanalization Times). Issue 12 (December 2016) - Ganesh, Aravind; Al-Ajlan, Fahad S.; Sabiq, Farahna; Assis, Zarina; Rempel, Jeremy L.; Butcher, Kenneth; Thornton, John; Kelly, Peter; Roy, Daniel; Poppe, Alexandre Y.; Jovin, Tudor G.; Devlin, Thomas; et al.
Abstract : Background and Purpose—: Infarct in a new previously unaffected territory (INT) is a potential complication of endovascular treatment. We applied a recently proposed methodology to identify and classify INTs in the ESCAPE randomized controlled trial (Endovascular Treatment for Small Core and Anterior Circulation Proximal Occlusion With Emphasis on Minimizing CT to Recanalization Times). Methods—: The core laboratory identified INTs on 24-hour follow-up imaging, blinded to treatment allocation, after assessing all baseline imaging. INTs were classified into 3 types (I–III) and 2 subtypes (A/B) based on size and if catheter manipulation was likely performed across the vessel territory ostium. Logistic regression was used to understand the effect of multiple a priori identified variables on INT occurrence. Ordinal logistic regression was used to analyze the effect of INTs on modified Rankin Scale shift at 90 days. Results—: From 308 patients included, 14 INTs (4.5% overall; 2.8% on follow-up noncontrast computed tomography, 11.7% on follow-up magnetic resonance imaging) were identified (5.0% in endovascular treatment arm versus 4.0% in control arm [ P =0.7]). The use of intravenous alteplase was associated with a 68% reduction in the odds of INT occurrence (3.0% with versus 9.1% without; odds ratio, 0.32; 95% confidence interval, 0.11–0.96; adjusted for age, sex, and treatment type). No other variables were associated with INTs. INT occurrence was associated with reduced probability of good clinical outcome (common odds ratio, 0.25; 95% confidence interval, 0.09–0.74; adjusted for age, type of treatment, and follow-up scan). Conclusions—: INTs are uncommon, detected more frequently on follow-up magnetic resonance imaging, and affect clinical outcome. In experienced centers, endovascular treatment is likely not causal, whereas intravenous alteplase may be therapeutic. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01778335. Abstract : Supplemental Digital Content is available in the text.